EFEKTIVITAS HYPNO-BREASTFEEDING DALAM MENGATASI KECEMASAN PADA IBU MENYUSUI DI TPMB BIDAN JEHANARA TAHUN 2025 - Jehanara, Jehanara; Syam, Heriza; Masitoh, Siti; Fitriana, Shentya (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2025)
Causes of breastfeeding failure are influenced by several factors, including socio-cultural factors, psychological factors, the mother's physical condition, and health workers. Psychological or mental factors can affect the smooth production of breast milk because a mother's feelings can either hinder or enhance the release of oxytocin, which is necessary for milk production. Therefore, hypno-breastfeeding can help make breastfeeding mothers feel more comfortable and reduce anxiety. This study aims to determine the effectiveness of hypno-breastfeeding in overcoming anxiety in breastfeeding mothers. This is a quantitative study with a quasi-experimental design involving an experimental group and a control group. The sample consisted of 66 respondents, with 33 breastfeeding mothers in each group. The instrument used to measure anxiety levels was the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data analysis was conducted through univariate analysis to describe the characteristics of respondents and bivariate analysis using independent T-test and dependent T-test to test the effectiveness of the intervention.The results of the independent t-test showed a significant difference between the experimental and control groups in reducing anxiety, with a p-value = 0.000 (p < 0.05) for the experimental group and a p-value = 0.326 (p > 0.05) for the control group. In addition, the results of the dependent T-test also indicated that hypno-breastfeeding was significantly effective in reducing anxiety levels in breastfeeding mothers (p-value = 0.000). It can thus be concluded that hypno-breastfeeding has an effect in overcoming anxiety in breastfeeding mothers at TPMB Bidan Jehanara in 2025.